Kewirausahaan Digital dan Penciptaan Nilai Berbasis Platform di Negara Berkembang: Peran Kemampuan Platform Digital dan Kemampuan Inovasi - Ika Rosalika; Syamsudin Syamsudin; Vera Agustina Yanti3 Warsino (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Digital transformation has fundamentally changed value creation mechanisms in entrepreneurial activities, particularly through the emergence of digital platforms that facilitate interactions among entrepreneurs, customers, and various actors within business ecosystems. This study aims to examine the effect of digital entrepreneurship on platform-based value creation in emerging economies by considering digital platform capability and innovation capability as important mechanisms influencing digital value generation processes. This research employs a quantitative approach using a survey method involving 240 entrepreneurs and small and medium-sized enterprise owners who actively utilize digital platforms in their business activities. The collected data were analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) through SmartPLS to examine the relationships among the proposed research constructs. The findings reveal that digital entrepreneurship has a positive and significant effect on digital platform capability, indicating that entrepreneurs’ abilities to identify digital opportunities, adopt technologies, and develop digital business models enhance their capacity to utilize digital platforms effectively. Furthermore, digital platform capability demonstrates a significant positive influence on platform-based value creation, suggesting that effective platform management enables entrepreneurs to generate value through digital networks, user interactions, and ecosystem collaboration. The study also confirms that digital entrepreneurship directly contributes to platform-based value creation, while innovation capability strengthens the relationship between digital platform capability and value creation outcomes. These findings contribute theoretically by integrating digital entrepreneurship theory, platform ecosystem theory, and dynamic capability perspectives to explain value creation processes in digital economies. Practically, this research provides implications for entrepreneurs, digital platform providers, and policymakers by emphasizing the importance of strengthening digital capabilities, innovation capacity, and supportive digital ecosystems to maximize entrepreneurial opportunities in emerging economies.